Pristine seas : journeys to the ocean's last wild places - Sala, Enric (Washington, D.C. : National Geographic, 2015)
"There are places in the ocean virtually untouched by man. They offer a fascinating glimpse into our past and an inspiring vision for the future. They are the last Pristine Seas, and National Geographic Explorer-in-Residence Enric Sala takes readers on an unforgettable journey to 10 of these astounding locations. From the shark-rich waters surrounding Coco Island, Costa Rica, to the iceberg-studded sea off Franz Josef Land, Russia, this incredible photographic collection showcases the thriving marine ecosystems that Sala is working to protect. Offering a rare glimpse into the world's underwater Edens, more than 200 images take you to the frontier of the Pristine Seas expeditions, where Sala's teams explore the breathtaking wildlife and habitats from the depths to the surface--thriving ecosystems with healthy corals and a kaleidoscopic variety of colorful fish and stunning creatures that have been protected from human interference. With this dazzling array of photographs that capture the beauty of the water and the incredible wildlife within it, this book shows us the brilliance of the sea in its natural state. It is a beautiful reminder of what we have to gain by protecting our seas"--
"National Geographic Explorer-in-Residence Enric Sala takes readers on an unforgettable journey to 10 places where the ocean is virtually untouched by man, offering a fascinating glimpse into our past and an inspiring vision for the future. From the shark-rich waters surrounding Coco Island, Costa Rica, to the iceberg-studded sea off Franz Josef Land, Russia, this incredible photographic collection showcases the thriving marine ecosystems that Sala is working to protect. Offering a rare glimpse into the world's underwater Edens, more than 200 images take you to the frontier of the Pristine Seas expeditions, where Sala's teams explore the breathtaking wildlife and habitats from the depths to the surface--thriving ecosystems with healthy corals and a kaleidoscopic variety of colorful fish and stunning creatures that have been protected from human interference. With this dazzling array of photographs that capture the beauty of the water and the incredible wildlife within it, this book shows us the brilliance of the sea in its natural state. Since 2005, Sala has been working to find, survey, and protect the last healthy, undisturbed places in the ocean from the Arctic to the South Pacific. Showcasing 10 of his designated pristine locations, this book will unveil the greatest discoveries from Sala and his team's expeditions and research. It is a beautiful reminder of what we have to gain by protecting our seas"--
Keywords: Ocean -- Pictorial works; Marine ecology -- Pictorial works; Marine biology -- Pictorial works; NATURE / Ecosystems & Habitats / Oceans & Seas; SCIENCE / Life Sciences / Biology / Marine Biology; PHOTOGRAPHY / Subjects & Themes / Plants & Animals